P74 Outcome of nodules detected during a healthy lung screening project. (12th November 2019) - Raghunath, S; Frost, F; Kutubudin, F; Mciver, A; Walshaw, M; Ledson, M
Abstract : Introduction: The Liverpool Healthy Lung Programme (LHLP) was designed to improve respiratory health and diagnose disease at an early stage. However, such programmes often produce unexpected findings, including nodules that require follow-up. We wished to look at the outcome for this subset of patients. Methods: We identified all patients attending the LHLP who were subsequently referred to our centre for nodule surveillance, and recorded the outcome in terms of imaging and ultimate diagnosis for those who have undergone repeat scans. Results: 191 patients were referred for nodule surveillance over a two year period (81, 3-month and 110, 12-month scans) : 42 still await an initial 12-month scan. Of those undergoing a 3-month scan, 16 required further scans (range 2–5), 1 had malignancy, and 7 have ongoing surveillance. Of those undergoing an initial 12-month scan, malignancy was excluded in 62 (3 required further scans), it was diagnosed in 2, and the remainder continue surveillance. Overall, 135/149 patients have completed nodule surveillance with no increase in size and require no further follow up. Of these, malignancy was ruled out in 124 (91.8%) after only a single further scan. 3 cancers (1, Stage III squamous cell carcinoma treated with radiotherapy, 1, Stage IV small cell lung carcinoma managed palliatively, and 1 Stage I large cell neuroendocrine cancer resected) were diagnosed. Discussion: Nodules detected during screening represent a challenge for screening programmes given that many are benign and patients may be exposed to unnecessary investigation and anxiety. Good nodule guidance has reduced the percentage of scans which enter surveillance. Our data confirms a low cancer detection rate (2.5%) in nodules referred from the LHLP setting. Reassuringly cancer could be excluded in 92% of patients after only one further scan, suggesting the harms from this approach are minimal for the vast majority of patients.